An open-source approach to automation in organic synthesis: The flow chemical formation of benzamides using an inline liquid-liquid extraction system and a homemade 3-axis autosampling/product-collection device. Issue 25 (21st June 2018) - O'Brien, Matthew; Hall, April; Schrauwen, John; van der Made, Joyce
Abstract: Several open-source hardware and software technologies (RAMPS, Python, PySerial, OpenCV) were used to control an automated flow chemical synthesis system. The system was used to effect the synthesis of a series of benzamides. An inexpensive Raspberry Pi single board computer provided an electronic interface between the control computer and the RAMPS motor driver boards. Graphical abstract: Image 1